Biotic potential of an exotic date palm pest specie: Oryctes agamemnon (Coleoptera: Scarabaeidae) - M’hammed Ehsine; Mohamed Sadok Belkadhi; Mohamed Chaieb (Journal of Oasis Agriculture and Sustainable Development, 2019)
In Tunisia, particularly in southern regions, the culture of date palms plays an important role, both at socioeconomic and ecological levels. In spite of its importance, this agro-system is still threatened by many species of insects and diseases. Among these phytosanitary problems figure the exotic pest Oryctes agamemnon. This insect causes severe damage on palm tree mainly on the collar and the root system. The aim of this work is to study some parameters of the biotic potential of the insect.  A number of ten couples were used in this survey. Follow-up of the experiment under the following conditions (Relative humidity = 40 +/- 6%, Temperature = 28 ° C +/- 2 ° C and a photoperiod: 16/8) allowed to study the reproductive potential, the larval survival rate and the adult lifetime.  The follow-up of the experiment shows that the average pre-oviposition period and the average post-oviposition period are 25.3 ± 9.85 and 7.3 ± 5.39 days, respectively. The developmental cycle comprises, the egg, 3 larval stages L1, L2 and L3, prenymph and nymph respectively lasted 13,742 ± 2,011 days, 26,591 ± 3,142 days, 43,361 ± 3,237 days, 137,047 ± 6,132 days, 7,487 ± 0,909 days and 21,390 ± 2,655 days. Survival rates for the various stages ranged from 83.631 to 93.886%. Adults lived on average 55.18 days for males and 60 days for females. The average number of eggs laid per female was 28.7 ± 17.13 with an average fertility rate of 81.184%.